Sosialisasi Demo Masak PMT Untuk Balita Gizi Kurang Dan Ibu Hamil KEK Kepada Kader Posyandu Di Wilayah Puskesmas Pacar Keling - Fachirunisa, Putri Nadia; Elvandari, Milliyantri; Wahju, Sutjipto Tri; Kurniansyah, Farizul Islam (Journal Of Human And Education (JAHE), 2024)
The impact of a lack of nutritional intake in pregnant women, besides being able to influence malnutrition in children, can also risk reducing the child's cognitive and physical development. One of the government's programs in an effort to overcome malnutrition experienced by mothers and babies is the need to implement supplementary feeding (PMT). Therefore, activities are needed to increase the knowledge and awareness of mothers of toddlers by increasing the knowledge of Posyandu cadres regarding malnutrition that can occur in pregnant women and toddlers. The socialization activity of PMT cooking demonstrations based on local food to posyandu cadres aims to increase insight and skills in modifying PMT menus. This research uses qualitative methods. Community service activities are carried out in the Keling Pacar Health Center working area. Pacar Keling Village, Tambaksari District, Surabaya City. There were 51 cadres attending the activity representing 21 Pacar Keling posyandu and 59 cadres representing 23 Pacar Kembang posyandu. The socialization of the PMT cooking demonstration based on local food was held on June 5 2024 at the RW X hall, Pacar Keling Village. Providing PMT education to posyandu cadres delivered by nutrition officers from the Pacar Keling Community Health Center. The material presented is in the form of an explanation of the meaning of local PMT, the aims, benefits, targets of PMT, and an example of a menu from local PMT, the nutritional content of the menu, and how to make it. The menu created in the cooking demonstration was "Croquettes Filled with Chicken and Scrambled Eggs", a PMT snack target for KEK Pregnant Women. Next there is "Anchovy Rice Balls Filled with Quail Eggs" for mothers of toddlers to prevent malnutrition in toddlers. It is hoped that the local PMT cooking demonstration activity for posyandu cadres can increase comprehensive understanding regarding the processing of local PMT which is healthy and nutritious for pregnant women and toddlers. So it can provide personal outreach to mothers under five and pregnant women who experience malnutrition by implementing local PMT in everyday life.